2017
DOI: 10.1016/j.ejca.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of primary tumour localisation in colorectal cancer treatment and outcomes

Abstract: Metastatic colorectal carcinoma (mCRC) is a heterogeneous disease with differing outcomes and clinical responses and poor prognosis. CRCs can be characterised by their primary tumour location within the colon. The left-sided colon, derived from the hindgut, includes the distal third of the transverse colon, splenic flexure, descending colon, sigmoid colon and rectum. The right-sided colon, derived from the midgut, includes the proximal two-thirds of the transverse colon, ascending colon and caecum. Sometimes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
217
3
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(237 citation statements)
references
References 49 publications
(112 reference statements)
8
217
3
9
Order By: Relevance
“…That role might be attributable to multiple factors, including clinical, molecular, and microbiome differences related to the side of the colon [77][78][79][80][81] . A recent systematic review and meta-analysis showed that ptl has prognostic value and that the risk of death is significantly lower in left-colon cancer [lcc (hr: 0.82; 95% ci: 0.79 to 0.84; p < 0.001)] 82 .…”
Section: Evidence Summarymentioning
confidence: 99%
“…That role might be attributable to multiple factors, including clinical, molecular, and microbiome differences related to the side of the colon [77][78][79][80][81] . A recent systematic review and meta-analysis showed that ptl has prognostic value and that the risk of death is significantly lower in left-colon cancer [lcc (hr: 0.82; 95% ci: 0.79 to 0.84; p < 0.001)] 82 .…”
Section: Evidence Summarymentioning
confidence: 99%
“…Current pivotal phase III clinical trials, such as FIRE‐3, CALGB80405 and TRIBE, have demonstrated that the overall survival (OS) in patients with wild‐type (WT) RAS mCRC is over 30.0 months, as compared to an OS of approximately 20.0 months in patients with mCRC whose tumors harbor a RAS MT and 13.4 months in patients with mCRC whose tumors harbor a BRAF V600E MT. Based on current knowledge, to maximize the effect of chemotherapy during the initial treatment, combination treatment with bevacizumab and chemotherapy is the preferred regimen for patients with right‐sided colorectal cancer (RCC) harboring WT RAS or patients with both left‐sided colorectal cancer (LCC) and RCC harboring MT RAS or MT BRAF , and combination treatment with an anti‐EGFR antibody and chemotherapy is considered for patients with LCC and both WT RAS and BRAF . Thus, detection of RAS and BRAF MTs before chemotherapy is recommended in various guidelines …”
Section: Introductionmentioning
confidence: 99%
“…Based on current knowledge, to maximize the effect of chemotherapy during the initial treatment, combination treatment with bevacizumab and chemotherapy is the preferred regimen for patients with right-sided colorectal cancer (RCC) harboring WT RAS or patients with both left-sided colorectal cancer (LCC) and RCC harboring MT RAS or MT BRAF, and combination treatment with an anti-EGFR antibody and chemotherapy is considered for patients with LCC and both WT RAS and BRAF. 8 Thus, detection of RAS and BRAF MTs before chemotherapy is recommended in various guidelines. [9][10][11] BRAF V600E is the most common BRAF MT, but BRAF non-V600E MTs account for >50% of RAF MTs in lung cancers 12 and occur in many other tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies reported differences between these "two" diseases in terms of incidence, microbiomes, chromosomal and molecular characteristics (i.e., high MSI and CIMP, KRAS mutation, BRAF mutation, PI3KCA mutation in a right-sided primary tumor), immunological features, and outcome. 13,38 In terms of liver metastases from colorectal cancer, the prognostic implication of primary tumor location remains unclear. An M.D.…”
Section: Discussionmentioning
confidence: 99%